Contextualising experiences of identity and belonging in the workplace: South African immigrants in the United States - Allen, Danielle Kyta (My University, 2020)
This qualitative study aimed to contribute to the cultural geography literature on migration in two ways: to enhance the limited knowledge of the South African immigrant experience in the United States (U.S.), and to further the understanding of the role and significance of the work setting as a social context for migration by situating and contextualising migrant experiences of identity and belonging in the workplace. Rich, qualitative data was gathered through in-depth interviewing with 18 South African immigrants living and working in the Northeast region of the U.S. The interviews allowed for an exploration of the subjective meanings and experiences of individuals in relation to immigrant identity and belonging, while staying attentive to articulations of context. This approach was informed by a recognition of the interrelatedness of place, identity, and belonging, the understanding of migrant belonging as relational, contextual, contingent, and dynamic, and through applying a place-based perspective of migration consistent with contemporary cultural geography literature. The study extends existing knowledge of South Africans as an immigrant group in the U.S. and brings more nuanced insight into their differential experiences. In particular, the findings indicate that South African immigrants’ advantageous positioning in the U.S. immigrant hierarchy and a relatively high level of social belonging may not equate with a strong personal sense of belonging. The study suggests that the workplace is a significant source of feelings of belonging for South African immigrants in America, providing meaning, identity, purpose, and connection. The findings of the study also enhance an understanding of the ways in which, and the circumstances under which, South African immigrant employees experience belonging in the American workplace. These include how intersecting dimensions of difference interact with workplace structures and discourses to position South Africans within their respective organisations; the workplace characteristics that enable or inhibit a sense of belonging for South African immigrant employees; and various strategies they may use to manage their difference and negotiate belonging at work
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2020